2016
DOI: 10.1159/000445942
|View full text |Cite
|
Sign up to set email alerts
|

Marked Reduction of the Number and Individual Volume of Sebaceous Glands in Psoriatic Lesions

Abstract: Background: Psoriasis is a chronic inflammatory skin disease characterized by plaques with inflammation, infiltration, hyper-/parakeratosis and desquamation. Microscopic findings in previous studies have revealed some degree of atrophy of the sebaceous glands in patients with psoriasis vulgaris and psoriatic alopecia. Objective: The aim of this study was to investigate possible changes of the sebaceous glands in patients with psoriatic plaques and especially psoriatic alopecia. Methods: Histological and stereo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
(38 reference statements)
1
11
0
1
Order By: Relevance
“…While earlier studies have shown SG atrophy in scalp psoriasis (Bardazzi et al, 1999, Headington et al, 1989, Silva et al, 2012, Werner et al, 2008, Wilson et al, 1994), here we document SG atrophy in psoriatic lesions at body sites other than the scalp. Similar findings have been reported very recently utilizing sequential vertical sections of PN and PP skin from scalp and back sites (Liakou, 2015), thus confirming our observations.…”
Section: Discussionsupporting
confidence: 93%
“…While earlier studies have shown SG atrophy in scalp psoriasis (Bardazzi et al, 1999, Headington et al, 1989, Silva et al, 2012, Werner et al, 2008, Wilson et al, 1994), here we document SG atrophy in psoriatic lesions at body sites other than the scalp. Similar findings have been reported very recently utilizing sequential vertical sections of PN and PP skin from scalp and back sites (Liakou, 2015), thus confirming our observations.…”
Section: Discussionsupporting
confidence: 93%
“…Antibiotics can be used to combat inflammatory acne, while retinoids, such as isotretinoin, are effective ‘comedolytics’, which reduce the number of comedones, lower sebum secretion, and cause SG involution (Dahlhoff, Zouboulis & Schneider, ; Kosmadaki & Katsambas, ). Atrophic SGs and altered sebaceous lipid composition have also been observed in patients with psoriasis and atopic dermatitis (Prose, ; Wirth, Gloor & Stoika, ; Burton & Pye, ; Werner, Brenner & Böer, ; Takahashi et al ., ; van Smeden et al ., ; Liakou et al ., ; Rittié et al ., ), suggesting that SG dysfunction may contribute to other inflammatory skin diseases (Shi et al ., ).…”
Section: Relevance Of the Brain–sebaceous Gland Axis To Skin Physiolomentioning
confidence: 99%
“…Since a thin section only shows one cross‐sectional image, it cannot capture the three‐dimensionally complex shape of a sebaceous gland. Creating volume data using serial sections can provide values of size but do not give a complete image of sebaceous glands . Using this methodology to create a complete image of a sebaceous gland would require much time and labor .…”
Section: Introductionmentioning
confidence: 99%
“…Creating volume data using serial sections can provide values of size but do not give a complete image of sebaceous glands. 19 Using this methodology to create a complete image of a sebaceous gland would require much time and labor. 13,14 For research of murine sebaceous glands, the whole mount technique is commonly used.…”
mentioning
confidence: 99%